On the performance of M-QAM optical signals in ROADM based optical networks - Simeão, Hélio Ferreira Paulo (2017)
The optical network physical layer limitations, in particular, the crosstalk due to imperfect isolation of optical network switching components, such as Reconfigurable Optical Add/Drop Multiplexers (ROADMs), can become a limiting factor in the performance of these networks. In this work, the impact of in-band crosstalk due to M-ary quadrature amplitude modulation (M-QAM) interferers on the performance of 4-QAM and 16-QAM coherent receivers in ROADM based networks is analysed, using Monte Carlo (MC) simulation. Several Wavelength Select Switch (WSS) models, a ROADM component, were studied, and each WSS model had a different optical filter profile. Two crosstalk metrics, unweighted crosstalk and weighted crosstalk, are used to measure the system performance degradation regarding the Optical Signal-to-Noise Ratio (OSNR) penalty at the coherent receiver. The difference between the two, is the fact that weighted crosstalk takes into account that the spectrum content closer to the center of the channel bandwidth has more impact than spectral content closer to the edges of the channel bandwidth. Using unweighted crosstalk metric, it can be concluded that optical filters with a wider rejection bandwidth in the center of the channel, have a better performance in terms of OSNR penalty at the coherent receiver. With the weighted crosstalk metric, it was observed that regardless of the WSS filter profile, the OSNR penalty performances of each WSS were similar. It can be concluded that the weighted crosstalk metric is very reliable at predicting system performances independently of the filter shape present in the WSS.